2020
DOI: 10.1007/s10008-020-04633-y
|View full text |Cite
|
Sign up to set email alerts
|

The Inverted Philosopher’s Stone: how to turn silver to a base metal

Abstract: Metals often are classified as “noble” or “base”—characterizing their reduction potential as one of the most important chemical properties. We show that metals are only as noble as allowed by their environment, i.e. this is a relative term, and the “frame of reference” simply is the solvent in which the redox system is present. We prove that silver is a prime example for a noble metal that forfeits its noble character in the simple ionic liquid HMIM Br (1-hexyl-3-methylimidazolium bromide) as an example for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…S5 and table S2). As the applicability of reference systems in ionic liquids is still under investigation, an exact determination of the absolute potentials is only possible to a limited extent ( 41 ). However, it still allows determining the decomposition voltage which can be obtained from the difference between oxidation and reduction potential.…”
Section: Resultsmentioning
confidence: 99%
“…S5 and table S2). As the applicability of reference systems in ionic liquids is still under investigation, an exact determination of the absolute potentials is only possible to a limited extent ( 41 ). However, it still allows determining the decomposition voltage which can be obtained from the difference between oxidation and reduction potential.…”
Section: Resultsmentioning
confidence: 99%
“…In AN, the redox potentials of the Ag + /Ag system and of the H + /H 2 system are exceptionally close together, thus indicating a similar solvation of Ag + ions and H + ions by AN. It was shown that the relationship between H + and Ag + solvation can be reversed: Ag + is more strongly solvated than H + in the ionic liquid 1‐hexyl‐3‐methylimidazolium bromide, i. e., silver is a “non‐precious” metal in this medium [53] . Concerning the Cl − ion, a comparatively weak solvation is observed in aprotic solvents: to force Cl − (by electronation of Cl 2 ) into solution, a comparatively low redox potential is already sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the relationship between H + and Ag + solvation can be reversed: Ag + is more strongly solvated than H + in the ionic liquid 1-hexyl-3-methylimidazolium bromide, i. e., silver is a "non-precious" metal in this medium. [53] Concerning the Cl À ion, a comparatively weak solvation is observed in aprotic solvents: to force Cl À (by electronation of Cl 2 ) into solution, a comparatively low redox potential is already sufficient. Thus, chlorine is a much weaker oxidant in aprotic solvents than in protic solvents, and in PC it is even a weaker oxidant than the Ag + ion.…”
Section: Cell IVmentioning
confidence: 99%